Evaluating Assisted Gene Flow in Marginal Populations of a High Mountain Species - Prieto-Benítez, Samuel; Morente-López, Javier; Rubio Teso, María Luisa; Lara-Romero, Carlos; García-Fernández, Alfredo; Torres, Elena; Iriondo, José María (Frontiers in Ecology and Evolution, 2021)
Many species cannot either migrate or adapt at the rate of temperature increases due to climate warming. Therefore, they need active conservation strategies to avoid extinction. Facilitated adaptation actions, such assisted gene flow, aim at the increase of the evolutionary resilience of species affected by global change. In elevational gradients, marginal populations at the lower elevation edges are experiencing earlier snowmelt and higher temperatures, which force them to adapt to the new conditions by modifying their phenology. In this context, advancing the onset of flowering and seed germination times are crucial to ensure reproductive success and increase seedling survival prior to summer drought. Assisted gene flow may bring adaptive alleles and increase genetic diversity that can help throughout ontogeny. The main aim of this work is to assess the effects that different gene flow treatments could have on the desired trait changes in marginal populations. Accordingly, we established a common garden experiment in which we assayed four different gene flow treatments between Silene ciliata Pourr. (Caryophyllaceae) populations located in similar and different elevation edges, belonging to the same and different mountains. As a control treatment, within-population crosses of low elevation edge populations were performed. The resulting seeds were sown and the germination and flowering onset dates of the resulting plants recorded, as well as the seedling survival. Gene flow between populations falling on the same mountain and same elevation and gene flow from high-elevation populations from a different mountain to low-elevation populations advanced seed germination time with respect to control crosses. No significant effects of gene flow on seedling survival were found. All the gene flow treatments delayed the onset of flowering with respect to control crosses and this effect was more pronounced in among-mountain gene flows. The results of this study highlight two important issues that should be thoroughly studied before attempting to apply assisted gene flow in practical conservation situations. Firstly, among-populations gene flow can trigger different responses in crucial traits throughout the ontogeny of plant species. Secondly, the population provenance of gene flow is determinant and plays a significant role on the effects of gene flow.